Saving Faces Changing Lives the Art of Maxillofacial Prosthodontics Case Series Comparing Two Different Materials - Ahmed, Bilal (Global Journal of Medical and Clinical Case Reports, 2014)
Surgical reconstruction of large facial defects is not possible at times due to extensive loss of tissues that cannot be corrected by surgery alone. In these cases, prosthetic restoration of lost facial tissues can be done using maxillofacial prostheses. Introduction of new material which gives life-like appearance to such prosthetic restorations e.g. silicone and poly ether rubbers and use of implants to retain these prostheses have given a new dimension to rehabilitation of such patients. However, in certain clinical scenarios, conventional acrylic resin prostheses are still the recommended options. This report discuss clinical performance of two cases of prosthetic rehabilitation of the nasal component of the face secondary to resection due to malignancy and due to infections using external device retained maxillofacial prosthesis.